2018
DOI: 10.5334/pb.392
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Language Switching Frequency on Attentional and Executive Functioning in Proficient Bilingual Adults

Abstract: Bilingual advantages in executive functions are well documented (see Bialystok, 2009; Dong & Li, 2015, for a review), but the specific aspects of bilingualism that underlie these advantages are unclear. The few studies conducted up until now on this subject (e.g., Hartanto & Yang, 2016; Prior & Gollan, 2011; Verreyt, Woumans, Vandelanotte, Szmalec, & Duyck, 2016) have suggested that the frequency of language switching may partially mediate this advantage. We further investigate the impact of oral language-swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…In line with these findings, Barbu et al (2018) also revealed that language-switching frequency enhances cognitive flexibility skills in bilingual adults. The authors compared two groups of proficient bilingual adults with different language-switching patterns, i.e., HFLSs and LFLSs, on a series of attentional and executive tasks assessing alertness, response inhibition, and cognitive flexibility.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In line with these findings, Barbu et al (2018) also revealed that language-switching frequency enhances cognitive flexibility skills in bilingual adults. The authors compared two groups of proficient bilingual adults with different language-switching patterns, i.e., HFLSs and LFLSs, on a series of attentional and executive tasks assessing alertness, response inhibition, and cognitive flexibility.…”
Section: Introductionsupporting
confidence: 78%
“…Alertness and response inhibition skills may be enhanced not by language-switching frequency but by bilingualism itself. Considering that the two bilingual groups (HFLSs and LFLSs) tested by Barbu et al (2018) had the same L2 proficiency levels, no significant group differences were observed in this respect given that these skills were probably used to the same extent as subjects became bilinguals.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, both Paap et al (2017) and Yim and Bialystok (2012) failed to find an association between their LSF measures and nonlinguistic task-switching costs. In contrast, yet similarly to Barbu et al (2018), we found that those participants who switched languages more often were faster (i.e., more efficient) when switching in a non-verbal switching task. Even though these four studies differ in several characteristics (e.g., participants' context, LSF measurement methods), one crucial aspect might explain the inconsistencies between results: the task-switching paradigm used.…”
Section: Discussionsupporting
confidence: 57%
“…Hence, it is expected that those bilinguals who are used to switch languages more often in similar contexts (i.e., dual-language context) experience larger effects on language switching and EC, since demands to their language control are greater than those experienced by single-language context bilinguals (Costa et al, 2009;Green & Abutalebi, 2013;Hartanto & Yang, 2016). In this vein, several studies have found associations between switching languages more frequently and better execution in different measures of non-verbal switching paradigms (Barbu et al, 2018;Becker et al, 2016;de Bruin et al, 2015;Hartanto & Yang, 2016;Prior & Gollan, 2011;Soveri et al, 2011). Furthermore, Verreyt et al (2016) studied the effect of LSF on inhibitory control abilities, showing that bilinguals who alternated between languages more often were more likely to evidence smaller congruency effects in tasks tapping into interference suppression (when PL2 was controlled for in the analyses).…”
Section: Introductionmentioning
confidence: 99%